Building inclusive and transformative education in Timor Leste - Moruk, Selviana Veronika; Freitas, Zelio da Conceiçăo (Universitas Ahmad Dahlan, 2025)
This research analyzes challenges and opportunities in developing inclusive and transformative education in Timor Leste. It faced challenges in building an education system that could reach all segments of society and promote social transformation. Using a qualitative approach through case studies in three districts—Dili, Baucau, and Oecusse, this research identified barriers in implementing inclusive education and explored innovative practices by schools and communities. The results showed significant progress in basic education access but highlighted gaps in quality and inclusion of marginalized groups. Collaborative approaches among the government, NGOs, and communities can create educational models suited to Timor Leste's socio-cultural context. The study emphasized strengthening teacher capacity, developing contextual curricula, and implementing supportive education policies. The results of this study are expected to contribute to the development of more responsive and effective education policies in Timor Leste, as well as add to the understanding of inclusive education in the context of post-conflict countries in general.